Kognitivni fenotip kod Neurofibromatoze tip 1 (Engrami, 2021)
Neurofibromatoses are a set of different genetic disorders that have a common characteristic of the appearance of nervous system tumors. There are three forms of the disease, of which type 1  neurofibromatosis (NF 1) is the most common. NF 1 is an inherited autosomal-dominant disease, with a high rate of new mutations. In addition to the many physical manifestations and complications that occur in persons with NF 1, there are also numerous cognitive difficulties, including lower general intellectual functioning, learning difficulties, but also problems in attention, visual abilities, executive functions, and speech. Attention disorders are up to three times more common in people with NF 1, while learning disabilities are present in more than half of these subjects. Disturbances in the field ofvisuospatial perception are recognizable even in the preschool period. About 80% of children with NF1 exhibitvarious speech and language disorders: slow early speech development, slower vocabulary enrichment, syntactic, semantic, and phonological speech disorders. Disruption of executive functions will manifest itself in the areas of working memory, organization, planning/problem-solving. This will reflect as the underperformance in academic achievement. Nearly one-third of these persons have emotionaland social problems.